2008
DOI: 10.1016/j.addr.2007.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and emerging technologies in the immunoisolation of cells and tissues

Abstract: Protection of transplanted cells from the host immune system using immunoisolation technology will be important in realizing the full potential of cell-based therapeutics. Microencapsulation of cells and cell aggregates has been the most widely explored immunoisolation strategy, but widespread clinical application of this technology has been limited, in part, by inadequate transport of nutrients, deleterious innate inflammatory responses, and immune recognition of encapsulated cells via indirect antigen presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
153
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 277 publications
(380 reference statements)
0
153
0
2
Order By: Relevance
“…It is expected that most planar and microencapsulation devices would demonstrate minimal fibroblast activation and fibrosis owing to their smooth outer layers. It has been reported that the geometry, rigidity and surface characteristics of biomaterial devices greatly influence macrophage proliferation and surface irregularities in the order of a few microns could trigger their differentiation into inflammatory phenotypes [114].…”
Section: Factors That Impact Bioencapsulationmentioning
confidence: 99%
“…It is expected that most planar and microencapsulation devices would demonstrate minimal fibroblast activation and fibrosis owing to their smooth outer layers. It has been reported that the geometry, rigidity and surface characteristics of biomaterial devices greatly influence macrophage proliferation and surface irregularities in the order of a few microns could trigger their differentiation into inflammatory phenotypes [114].…”
Section: Factors That Impact Bioencapsulationmentioning
confidence: 99%
“…[7][8][9] However, in microencapsulation, the cells are surrounded by a membrane that is typically more than O(100) lm in thickness. The large thickness of the membrane results in long chemical diffusion times that may adversely affect cell survival and function 10 and prevent rapid response of the cells to physiological stimuli. Another particle coating geometry-so-called conformal coating-involves depositing a much thinner layer of a protective membrane on microparticles or cell aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…This coating geometry reduces molecular transport times through the membrane, and the homogeneous thickness of the coating layer permits uniform transport of molecules to the particle surface. 10 Conformal coating has been reported using several two-phase flow techniques, namely, selective withdrawal, 13,14 centrifugation, 15 and bulk emulsification. 16 In addition to these hydrodynamics-based methods, other conformal coating techniques that involve surface chemistry include interfacial polymerization, 17 surface binding with polymer-lipid, 18,19 and layer-bylayer poly(L-lysine)(PLL)-PEG copolymer assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Islet encapsulation strategies to date have mainly focused on macrocapsules (encapsulation of the whole islet graft) and microcapsules (encapsulation of individual islets) [7]. Previous studies in animal models [8,9] and in human participants [10,11] have demonstrated that physical isolation of islets from the host immune system by, for example, alginate microencapsulation is effective in preventing beta cell loss and in maintaining long-term secretory function in transplanted allogeneic and xenogeneic islets without systemic immunosuppression [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Conformal nano-coating avoids these problems by generating a biocompatible nanometre-scale isolating layer close to the cell surface, thus reducing barriers to diffusion, while ensuring that the encapsulated islets can be implanted into any site suitable for non-encapsulated islets [7]. The challenge with conformal nano-coating is to nano-engineer an efficient and lasting immune-protective layer that covers islets completely or nearly completely, and is biocompatible with the recipient.…”
Section: Introductionmentioning
confidence: 99%